The 2010 Tennis Anti-Doping Programme - Miller, S. (Medicine and Science in Tennis, 2010)
In 2009, there were substantial changes to the Tennis Anti-Doping Programme (TADP), mainly because of the introduction of a revised WADA Code. By comparison, the changes to the 2010 TADP are relatively few number, and mainly clarifications rather than major changes. This article summarizes the main changes to the TADP for 2010.